2016
DOI: 10.11648/j.js.s.2016040301.17
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ligasure Sealing Versus Conventional Suture - Ligation in Total Thyroidectomy

Abstract: Introduction:Effective vessel haemostasis can be achieved by suture knot tying technique or newer techniques of vessel haemostasis like ligasure as an alternative bipolar surgical diathermy system. Various diathermy techniques have been proposed to reduce intraoperative blood loss in surgery and the new electrothermal bipolar tissue sealing system (Ligasure) has been applied in various specialties of surgery. The objective of this randomized study was to compare the outcome of ligasure versus conventional clam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
(31 reference statements)
4
8
0
Order By: Relevance
“…Many researchers have reported results similar to our study. These studies demonstrated statistically significant (p<0.005) difference in intraoperative bleeding between LigaSure small jaw group and conventional technique group [17,19,22,24]. In our study there was only one case of postoperative hematoma formation in the conventional vascular ligation group (0.9%) while none of the patients in the LigaSure group developed hematoma formation (p>0.05).…”
Section: The Effectiveness and Safety Of Ebds Like Harmonic-scalpel® supporting
confidence: 41%
“…Many researchers have reported results similar to our study. These studies demonstrated statistically significant (p<0.005) difference in intraoperative bleeding between LigaSure small jaw group and conventional technique group [17,19,22,24]. In our study there was only one case of postoperative hematoma formation in the conventional vascular ligation group (0.9%) while none of the patients in the LigaSure group developed hematoma formation (p>0.05).…”
Section: The Effectiveness and Safety Of Ebds Like Harmonic-scalpel® supporting
confidence: 41%
“…The use of the LigaSure TM Small Jaw device in complete total thyroidectomy has been shown to be safe and effective in reducing operative time, intraoperative blood loss and postoperative fluid drainage. This sealing device yields better results regarding the function of the recurrent laryngeal nerves and the condition of the parathyroid glands (7,8) The Thunderbeat TM Open Fine Jaw is the only device currently available in the world capable of simultaneously providing frictional thermal energy through ultrasound and bipolar power generation (9). Years of study on this device have shown that this combination of bipolar and ultrasonic energy is more beneficial in surgery compared to devices using only ultrasound (Harmonic Focus TM ) or only bipolar energy (LigaSure TM Small Jaw).…”
Section: Discussionmentioning
confidence: 98%
“…However, many researchers reported significant reduction of intraoperative blood loss by the use of LigaSure system in total thyroidectomy when compared with the conventional suture ligation technique. [171819] With a reduced blood loss and secured hemostasis provided by the LigaSure Vessel Sealing System, there may not be need for routine grouping and cross-matching of blood for all thyroid surgery again as has been the practice in our center.…”
Section: Discussionmentioning
confidence: 99%